Anaemia and malnutrition in children aged 0–59 months on the Bijagós Archipelago, Guinea-Bissau, West Africa: a cross-sectional, population-based study. (August 2013) - Thorne, C J; Roberts, L M; Edwards, D R; Haque, M S; Cumbassa, A; Last, A R
Abstract : Background: Childhood malnutrition is the leading risk factor for the global burden of disease. Guinea-Bissau is a politically unstable country with high levels of childhood malnutrition and mortality. Aim: To determine the nutritional status of children on three remote islands of the Bijagós Archipelago, Bubaque, Rubane and Soga, and to identify factors associated with malnutrition and anaemia in this population in order to provide a baseline for future public health interventions. Methods: A cross-sectional, population-based, door-to-door household survey of randomly selected households was undertaken to collect data on children aged 0–59 months ( n = 872). Dietary information was collected using a validated questionnaire. Anthropometric measurements were collected using World Health Organization techniques. Capillary blood samples were analysed using a Hemocue®, with anaemia defined as Hb<11 g/dl. Results: The prevalences of stunted, wasted and underweight children were 21·8%, 9·4% and 3·7%, respectively. These figures indicate moderate chronic malnutrition. The significant predictor variables for stunting were: age in months (OR 1·03), rural residence (OR 2·32), anaemia (OR 3·55) and residence on Soga island (OR 0·44). Stunting was more prevalent in males (25·4%) than in females (18·6%) ( P = 0·03). The prevalence of anaemia was 80·2%. Age (OR 0·96), male gender (OR 1·81) and stunting (OR 2·87) were significant predictors. The Minimum Acceptable Diet was achieved by only 8·7% of children. Conclusion: The prevalence of malnutrition on the Bijagós Archipelago is less than half that on the mainland. This study is the first to determine the prevalence of anaemia in Guinea-Bissau, which, at 80·2%, is of severe public health concern. Future research should focus on the aetiology of stunting and anaemia, especially the contribution of infectious diseases and mother–child interaction. Iron supplementation should be strongly considered in this population.